The Challenge of Designing New Work Systems Towards Effective e-Health Interventions - Duarte de Almeida, I.; M.J. Delgado (Advances in Intelligent Systems and Computing, 2020)
The design of novel mobile applications for healthcare improves access, convenience, education, care-quality/effectiveness. To increase the cost-value of the integrated healthcare system, new health-related work design should be developed. As the patients are more informed and take an active control decision about their healthcare options, they force the healthcare systems to redesign and change inevitably. The patient empowerment lies to the access of different clinical outcomes information: diseases reliable information, available treatments and management of therapeutical outcomes. This needs to be aligned with caregivers, providers and financiers. Our overall objective is to understand how the Portuguese population will respond to eHealth technology design and development for information exchange within healthcare systems and how the healthcare systems cope with new work systems design. Four core interactive work design features were identified that may mediate the effects of intervention in the healthcare outcomes: Social context and support, Contacts with intervention, Tailoring, and Self-management.